PENGARUH VARIASI WAKTU PELAPISAN TiN HASIL DEPOSISI DC REACTIVE MAGNETRON SPUTTERING TERHADAP KEKERASAN, LAJU KOROSI, KEAUSAN ABRASI DAN KEKASARAN BAJA TAHAN KARAT MARTENSITIK AISI 410 - , Xander Salahudin; , Dr. Ir. Viktor Malau, DEA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
AISI 410 stainless steel is widely used for medical equipments because of its corrosion resistancy, but it doesnât have a high hardness value. Surface modification is a method to improve the surface characteristics of the material, such as hardness, wear and corrosion resistancy. The application of titanium nitride (TiN) as a thin layer will improve the properties of AISI 410 stainless steel, as TiN has high hardness, high chemical stability and good adhesion bonding with the substrate. This study aim at studying the effect of a TiN thin layer that deposited by DC magnetron reactive sputtering on surface of AISI 410 to hardness, corrosion rate, abrasive wear and roughness. The deposition process used a DC magnetron sputtering machine with constant variables are current of 80 mA, voltage of 0,4 kV, chamber pressure of 4 x 10-2 torr, pressure ratio of Ti: N = 17:3, and substrate-specimen distance of 12 mm. The experiment was carried out by varying the deposition time of 30, 40, 50, 60 and 70 minutes. The hardness test used a micro-Vickers hardness tester, the corrosion test used a galvanostat PGS 201T with testing media 0,9% NaCl, the abrasive wear test used an ogoshi high speed universal wear testing machine OAT-U and the roughness test used a surface roughness instrument SE 1700. The results of this study indicate that the hardness value will increase with longer deposition time and then its decrease after reaching the highest hardness, where the highest hardness value is obtained at the deposition time of 50 minutes with an average hardness value 245,28 VHN0,01. The corrosion rate and abrasive wear will decrease with longer deposition time and then its increase after reaching the optimum conditions. The lowest corrosion rate and the lowest abrasive wear are obtained at the deposition time of 50 minutes, with the average corrosion rate is 2,2 mm/yr and the average abrasive wear is 2,6 x 10-6mm3/kg.m. The roughness value does not show a significant difference between the raw material and the AISI 410 stainless steel which has been deposited with TiN.